2013
DOI: 10.1523/jneurosci.2561-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Transthyretin Inhibition of β-Amyloid AggregationIn Vitro

Abstract: Tissue-specific overexpression of the human systemic amyloid precursor transthyretin (TTR) ameliorates Alzheimer's disease (AD) phenotypes in APP23 mice. TTR-␤-amyloid (A␤) complexes have been isolated from APP23 and some human AD brains. We now show that substoichiometric concentrations of TTR tetramers suppress A␤ aggregation in vitro via an interaction between the thyroxine binding pocket of the TTR tetramer and A␤ residues 18 -21 (nuclear magnetic resonance and epitope mapping). The K D is micromolar, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
194
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(212 citation statements)
references
References 52 publications
18
194
0
Order By: Relevance
“…However, results obtained by other authors suggest that it is the monomeric form of TTR that preferentially binds Aβ (20), especially when the peptide is in oligomeric form (21). The monomeric form of TTR was also shown to be the most efficient at inhibiting Aβ fibril formation, although by isotherm titration calorimetry (ITC), the monomeric TTR did not exhibit any sign of binding to Aβ, contrary to the tetramer (21). Also, it has been shown that Aβ oligomerrelated toxicity can be neutralized by the binding of TTR (especially monomeric TTR) by promoting their assembly into larger nontoxic species (22).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…However, results obtained by other authors suggest that it is the monomeric form of TTR that preferentially binds Aβ (20), especially when the peptide is in oligomeric form (21). The monomeric form of TTR was also shown to be the most efficient at inhibiting Aβ fibril formation, although by isotherm titration calorimetry (ITC), the monomeric TTR did not exhibit any sign of binding to Aβ, contrary to the tetramer (21). Also, it has been shown that Aβ oligomerrelated toxicity can be neutralized by the binding of TTR (especially monomeric TTR) by promoting their assembly into larger nontoxic species (22).…”
mentioning
confidence: 89%
“…Importantly, in vivo administration of one such drug resulted in the amelioration of AD features (19). However, results obtained by other authors suggest that it is the monomeric form of TTR that preferentially binds Aβ (20), especially when the peptide is in oligomeric form (21). The monomeric form of TTR was also shown to be the most efficient at inhibiting Aβ fibril formation, although by isotherm titration calorimetry (ITC), the monomeric TTR did not exhibit any sign of binding to Aβ, contrary to the tetramer (21).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Besides its transporter functions, TTR is implicated in a wide variety of additional physiological processes, such as thermoregulation and endocrine roles, and is produced at several sites. In addition, it has been shown to exert protease activity and chaperonelike actions (3,4), which may provide links between TTR and Alzheimer's disease (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the activity of Brichos is reminiscent of the ability of transthyretin (TTR), an abundant extracellular protein secreted from the liver and the choroid plexus, which has also been shown to reduce Ab aggregation (Li et al, 2013). Brichos and related amyloid chaperone managers belong to what we have defined as the ''outside'' proteostatic network (Powers and Balch, 2011).…”
mentioning
confidence: 99%